Development and validation of the self-rating of biological rhythm disorder for Chinese adolescents. (1st February 2022) - Xie, Yang; Wu, Xiaoyan; Tao, Shuman; Wan, Yuhui; Tao, Fangbiao
ABSTRACT: Modern lifestyles, and the popularization of artificial light at night, have led to maladjusted social time and internal circadian rhythm, so developing an instrument on biological rhythms is critical. A 36-item self-rated questionnaire assessing biological rhythm disorder in adolescents was developed according to the literature and expert evaluations. Based on a literature review, four dimensions, digital media use, sleep, eating habits, and activity, were determined. After preliminary item analysis, seven unqualified items were eliminated. A total of 1, 152 college students and 8, 082 middle school students were selected. Two independent sample t- tests, the Pearson correlations, and confirmatory factor analysis, were used to evaluate the reliability and validity of the questionnaire. The final questionnaire consisted of 4 dimensions covering 29 items, and the variance cumulative contribution was 62.65%. Cronbach's α for the total questionnaire was 0.950 and ranged from 0.817 to 0.904 for each dimension. The Pearson correlation coefficients between each item and the total score ranged from 0.360 to 0.755, and the Pearson correlation coefficient between each item and its dimension was between 0.575 and 0.841. Confirmatory factor analysis showed that the indices of CFI, TLI and RMSEA were 0.911, 0.901 and 0.043, respectively, which is a good degree of fit. The self-rating scale is consistent with the evaluation standard of psychometrics and can be used to evaluate the degree of biological rhythm disorder in adolescents.